Propuesta de mejora del proceso de producción de Baldosa en la UEB de Hormigón y Carpintería de Pinar del Rio. - Terán Herrera, Julio Vinicio (2012)
The thesis was carried out in the UEB Concrete and Carpentry, belonging to the Company Building supplies which elaborates a range of products of the construction such us, Tile for floors, concrete Block, hydraulic losetas, tubes of sewer systems, terrazos elements, wooden elements among others, in the province of Pinar del Río (Cuba). Located in the 2 ½ km of the highway to San Juan and Martínez, in the Industrial Area 7 Undergrowth. In this investigation a diagnosis of the current situation of the productive flow of the tile production was executed and the different steps were analyzed of each one of the processes of the tile. The objective of the investigation is to analyze the productive tile process of the U.E.B “Complex of Concrete and Carpentry” for the reengineering of processes. To give execution to the same one the following specific objectives, they were traced: to know the methodology for the production of the tile, to describe the process of tile production, to determine the maximum production to obtain with the installed capacities, to detect the main problems that affect the production and to propose solutions to the detected problems.